RANCANG BANGUN SISTEM PENERIMAAN PESERTA DIDIK BARU DAN PROSES SELEKSI AKADEMIK BERBASIS WEB PADA SMK EBEN HAEZER - Simamora, Marta magdalena; Ridho, Muhammat Rasid (LPPM Universitas Putera Batam, 2024)
This research focuses on designing and implementing a Web-Based New Student Admission and Academic Selection System for SMK Eben Haezer. The system aims to enhance the efficiency and transparency of the admission process. Leveraging web-based technology, the system features an online registration form, integration with the student database, an automated academic selection workflow, and a real-time monitoring dashboard for administrators. Emphasizing data security and selection process integrity, the system aims to optimize the overall experience for both administrators and applicants. The outcomes of this research are expected to significantly contribute to streamlining the admission and academic selection processes at SMK Eben Haezer. The web-based system seeks to improve user experience, expedite data processing, and ensure a more efficient and transparent selection of new students. Keywords: Information; School; Academic; System; Web;